A case of mid‐ureteral stricture with ipsilateral atrophic kidney in a young adult - Arisa Machida; Masakazu Abe; Shuhei Ishii; Kie Sekiguchi; Kenta Takahashi; Ei Shiomi; Shigekatsu Maekawa; Yoichiro Kato; Noriyuki Uesugi; Wataru Obara (IJU Case Reports, 2023)
Introduction Most congenital ureteral strictures occur at the ureteropelvic or ureterovesical junction in children. Mid‐ureteral stricture is very rare and can cause congenital hydronephrosis. Only a few studies have reported on coexisting mid‐ureteral stricture with ipsilateral atrophic kidney in young adults. Case presentation A 16‐year‐old girl presented with repeated urinary tract infection. Computed tomography revealed a right atrophic kidney and hydroureter. Retrograde pyelography showed a mid‐ureteral stricture. Laparoscopic nephroureterectomy was performed, and histological examination revealed mid‐ureteral stricture with hyperplasia of the fibrous connective tissue and an atrophic kidney. Conclusion Mid‐ureteral stricture in a young adult is extremely rare. Appropriate imaging studies including retrograde pyelography are necessary for accurate diagnosis of mid‐ureteral stricture.